Strategic Plan Implementation Drivers and Performance of Gusii Water and Sanitation Company (GWASCO) - Omeru, Evans; Juma, Dennis (Journal of Business and Strategic Management, 2025)
Purpose: This study sought to examine the effect of strategic plans implementation drivers on performance at Gusii Water and Sanitation Company (GWASCO). Specifically, the study investigated the influence of leadership involvement, resource allocation, employee participation, and monitoring and evaluation on organizational performance. Methodology: A descriptive research design was adopted, primary and secondary data was collected using structured questionnaires administered to GWASCO employees. The target population included departmental heads, supervisors, and operational staff. Data was analyzed using both descriptive and inferential statistics, including correlation and regression analysis, to determine the relationships between the independent variables and performance outcomes. Findings: Through regression analysis, the study found that all four factors Leadership Involvement, Resource Allocation, Employee Participation, and Monitoring and Evaluation had a positive and statistically significant impact on organizational performance. Among these, Monitoring and Evaluation emerged as the most influential factor, followed by Leadership Involvement, Employee Participation, and Resource Allocation. The regression model explained 74% of the variance in performance, with the overall model being statistically significant (p-value = 0.000). Unique Contribution to Theory, Policy and Practice: The study recommends that organizations focus on strengthening these areas to enhance performance and sustain long-term success. Additionally, future research could explore industry-specific dynamics, the role of technology, and the influence of organizational culture in shaping these relationships.